2021
DOI: 10.3390/foods10102363
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-Assisted Extraction and Structural Characterization of Chondroitin Sulfate Derived from Jumbo Squid Cartilage

Abstract: Chondroitin sulfate (ChS) is usually used as an oral nutraceutical supplement, and has been popular in Asia, Europe, and United States for many years. In this study, a potential and sustainable source of ChS from jumbo squid (Dosidicus gigas) cartilage was explored; ultrasound-assisted extraction (UAE) was used to extract ChS from jumbo squid cartilage. The result of mass transfer coefficients based on Fick’s law showed that UAE had higher mass transfer efficacy. The response surface methodology (RSM) combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The yields (based on the dry weight) obtained revealed that the heads (8.1%) were the best substrates followed by the skin (3.7%) and bones (1.4%). These variations in yields can result from a variety of factors such as fish species, sample preparation conditions, and extraction techniques [19]. For comparative purposes, the obtained yields of GAGs that were recovered from the heads and bones of S. canicula were around 6% and 2%, respectively [20].…”
Section: Extraction Purification and Chemical Composition Of Gagsmentioning
confidence: 99%
See 1 more Smart Citation
“…The yields (based on the dry weight) obtained revealed that the heads (8.1%) were the best substrates followed by the skin (3.7%) and bones (1.4%). These variations in yields can result from a variety of factors such as fish species, sample preparation conditions, and extraction techniques [19]. For comparative purposes, the obtained yields of GAGs that were recovered from the heads and bones of S. canicula were around 6% and 2%, respectively [20].…”
Section: Extraction Purification and Chemical Composition Of Gagsmentioning
confidence: 99%
“…According to previous studies, CS derived from cartilaginous fishes generally shows molecular weight values between 50 and 70 kDa. On the contrary, CS purified from terrestrial sources has a lower molecular weight that ranges between 13 and 26 kDa [19].…”
Section: Molecular Weight Analysis Of Gagsmentioning
confidence: 99%
“…44 Using this technique, CS has been extracted from jumbo squid cartilage. 45 CS belongs to the representative GAGs and consists of repeated disaccharide units of GalNAc and GlcA. 46 According to the disaccharide composition, CS is commonly split into CS-O(non-sulphated CS), CS-A, CS-B, CS-C, CS-D, and CS-E (as demonstrated in Fig.…”
Section: Extraction Of Csmentioning
confidence: 99%
“…Chondroitin sulfate can be extracted from shark or jumbo squid cartilage. 29 The anionic character of ChS allows the formation of nano-PEC structures with ChI through electrostatic interactions. 21 Thus, utilizing nano-capsules made from ChS-ChI shell to protect unstable nutrients, such as CBLO, may increase its resistance to UV irradiation, oxidation, and high temperatures, while reducing unpleasant odors.…”
Section: Introductionmentioning
confidence: 99%
“…Chondroitin sulfate (ChS) is a natural polysaccharide that consists of an alternating unit of β ‐(1,4)‐ d ‐glucuronic acid and β ‐(1,3)‐ N ‐acetyl‐ d ‐galactosamine, sulfated at different carbon positions. Chondroitin sulfate can be extracted from shark or jumbo squid cartilage 29 . The anionic character of ChS allows the formation of nano‐PEC structures with ChI through electrostatic interactions 21 .…”
Section: Introductionmentioning
confidence: 99%